Learning Patterns during the Disruptive Situation in Informal Education: Parents’ Efforts and Challenges in the Adjustment of Progressive Learning - Koesoemo Ratih; Muhammad Fahmi Johan Syah; Nurhidayat Nurhidayat; Sally Jarin; Jenny Buckworth (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This study investigates informal learning during the Covid-19 pandemic in Indonesia. Distant learning during the Covid 19 pandemic affects all aspects of education, including parents’ roles that switch to be teachers at home. This condition enables new learning patterns in order to offer children learning opportunities in their home. This study employs a qualitative approach with ethnographic design. The data collection techniques used an open observation guide which was examined for its validity using face and content validity. The techniques of analyzing data included data analysis across sites with some analysis components of data collection, reduction and conclusion. The research findings, in the form of description and formulation of learning patterns reveal adaptive ways to deliver effective education for children. In this way, they are prepared for 21st century skills and to face the industrial revolution 4.0 and society 5.0 in these disruptive times. This pandemic situation forms significant roles of parents in educating their children and strengthen-ing them in facing learning problems. Several parents’ roles include educators, facilitators, tutors, motivators, models, and controllers. Their roles can create pleasant learning situation for their children in the current pandemic situation. The multiroles of parents at home are key to keeping a good learning environment with their children. Therefore, parents are the keys to the success of child education during the Covid 19 Pandemic.